PEMBUATAN GAME PLATFORMER “MEDICAL ATTACK” MENGGUNAKAN UNITY - Franky Sutanto; Jeanny Pragantha; Rendi Kristyadi (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Game "Medical Attack" is a platformer game genre. The purpose of this game is to provide entertainment and introduction to drugs which cure the disease. Player acts as a drug robot called Zmap which will kill the disease in the form of viruses and bacteria inside in the human body. This games was developed by Unity game engine and C#  programming language. Player must pass through each stage by using the weapon of the appropriate antibiotic shots, to defeat the enemy and boss at each stage. The game is tested by blackbox testing, alpha testing by the supervisor, and beta testing through a survey of 20 users. The test results indicate that the game "Medical Attack" is a game that is quite challenging, entertaining, easily understood by the user and provide information about drugs and diseases.